An audit of “Repeat” fine needle aspiration cytology procedures in a cytopathology laboratory—An important quality indicator - Shivali Sehgal; Sujata Jetley; Sabina Khan; Zeeba S. Jairajpuri (MGM Journal of Medical Sciences)
Background: The cytopathology department mainly conducts audits to evaluate the diagnostic efficiency of procedures across different organs. However, the common occurrence of repeat aspirations, typical in many cytology laboratories, has largely been overlooked. This study sought to examine the frequency of repeat Fine Needle Aspiration Cytology (FNAC) procedures within a cytopathology laboratory and to explore the root causes for such repetition. Materials and Methods: A retrospective descriptive analysis was conducted at the cytopathology laboratory affiliated with a tertiary care facility. This study included all FNAC cases reported over six months. Data were extracted from cytology records, and multiple factors leading to repeat aspirations were examined. The rate of repeat FNAC procedures was calculated by dividing the number of “repeat” FNAC procedures in a specific month by the total number of FNACs performed. A quality manager set a benchmark of 15% for the repeat FNAC rate. Results: About 39 out of 303 FNACs (12.8%) were repeated for 6 months. Soft tissue lesions, predominantly lipomas, accounted for most (35.9%) of these repeated aspirations. The principal reason for the need for repeat aspirations was insufficient material obtained during the initial aspiration. Conclusion: In many laboratories, the frequency of repeat FNAC procedures and their root causes often need to be checked. Evaluating the quantity of repeat aspirations in a laboratory indicates its performance and is a vital quality measure, especially when accreditation is required. This research proved beneficial by providing valuable insights into the prevalence of repeat aspirations within a cytology laboratory.